Development and Application of Digital Maxillofacial Surgery System Based on Mixed Reality Technology - Yang, Rong; Li, Chenyao; Tu, Puxun; Ahmed, Abdelrehem; Ji, Tong; Chen, Xiaojun (Frontiers in Surgery, 2022)
Abstract: Objective: To realize the three-dimensional visual output of surgical navigation information by studying the cross-linking of mixed reality display devices and high-precision optical navigators. Methods: Applying quaternion-based point alignment algorithms to realize the positioning configuration of mixed reality display devices,high-precision optical navigators, real-time patient tracking and calibration technology; based on open source SDK and development tools, developing mixed reality surgery based on visual positioning and tracking system. Results: Realized the cross-linking of mixed reality display equipment and high-precision optical navigator, developed a digital maxillofacial surgery system based on mixed reality technology and successfully implemented mixed reality-assisted tumor resection and reconstruction in 4 cases. Conclusions: The maxillofacial digital surgery system based on mixed reality technology can superimpose and display three-dimensional navigation information in the surgeon's field of vision. Moreover, it solves the problem of visual conversion and space conversion of the existing navigation system. It improves the work efficiency of digitally assisted surgery, effectively reduces the surgeon’s dependence on spatial experience and imagination, and protects important anatomical structures during surgery.It is a significant clinical application value and potential.